The Role of Internal Control Over Non-Financial Non-Current Assets (Fixed Assets) in Preserving Public Money in the Kingdom of Saudi Arabia: Applied Study in the Public Sector - Al-Aamry, Noura Hassan; Ibrahim, Nahla Mohamed El-Sayed (The Arab Journal of Administration, 2024)
The study relied on the analytical descriptive approach based on data collection, representing the sample of the study in institutions operating in the public sector in Saudi Arabia. Which amounted to (27) institutions, whose fiscal year ends on 12/31 of each year and whose financial reports and all data are available, has reached the number of individuals who responded to the questionnaire distributed 120 individuals, and the two researchers used the questionnaire as an essential tool for data collection, The study found that an integrated documentary course and sound financial and control rules and procedures are applied to non-financial assets in government agencies in Saudi Arabia and there are no statistically significant differences in the role of internal control over non-current non-financial assets according to personal and functional variables.